Frequency of Anemia in Type 1 Diabetic Adolescent Patients in Tertiary Care Hospital of Karachi, Pakistan: Frequency of Anemia in Type 1 Diabetic Adolescent Patients - Uddin, Sagheer; Hameed, Taif; Ali, Sana Barkat; Saeed, Muhmmad; Anjum, Aroosa; Mubarak, Mir (Pakistan Journal of Health Sciences, 2025)
Anemia in type 1 diabetes (T1D) can impair glucose management by reducing red blood cells, reducing oxygen delivery and affecting insulin sensitivity. Low hemoglobin levels may cause falsely higher HbA1c readings, misleading healthcare providers about glycemic control. Objective: To determine the frequency of anemia in type 1 diabetic adolescent patients. Methods: A cross-section study was conducted at Baqai Medical University, Karachi, from April 2023 to November 2023. The sample size was 169 diagnosed type 1 diabetes patients. After getting informed consent, HbA1c and Complete Blood Count (CBC) were measured. In the CBC of individuals with hypochromic microcytic anemia, the particular subjects underwent further investigation of serum iron, ferritin and total iron binding capacity (TIBC) levels. All data analyses were performed on SPSS version 23.0. Results: The study analyzed adolescent T1Dpatients, focusing on their age and anthropometric parameters. Out of 169 type 1 diabetes patients, 81 were diagnosed with anemia while 88 weren’t. There is a statistically significant difference in anthropometric parameters among anemic and non-anemic type T1D patients. The hematological parameters between T1Dsubjects with anemic and non-anemic were significantly lower in those with anemia, with p-values of 0.000**. Out of 81 anemic patients, 47 had iron deficiency anemia with lower levels of iron and ferritin and higher levels of TIBC. Conclusions: It was concluded that the study highlights a substantial prevalence of anemia among adolescents with T1D. Hematological analysis showed lower blood parameters and higher TIBC in anemic patients. HbA1c is higher in anemic T1D patients than in non-anemic ones.